ANALISIS RISIKO BAHAYA DI PT. PEMBANGUNAN PERUMAHAN (PERSERO) TBK. PADA PROYEK PEMBANGUNAN BENDUNGAN TIU SUNTUK MENGGUNAKAN METODE HIRARC - Nurul Hudaningsih; Fauzi, Rival; Adiasa, Iksan (Hexagon Jurnal Teknik dan Sains, 2024)
The K3 management system is part of the company management system in the context of risk control to minimize dangers in the workplace. Work accidents can cause losses in time, wealth, property and lives. Accidents have causes so it is necessary to control and repair work places, tools and processes. This research was conducted using the HIRARC (Hazard Identification Risk Assessment and Risk Control) method to identify hazards that can occur in each job. In the preparation of HIRARC it is divided into three stages, where the first stage is hazard identification, then risk assessment, and the next stage is the risk control stage. The result of hazard identification is that there are several potential hazards in the work place and attitude. After carrying out a risk assessment, the risk level obtained before controlling the shootcreet work process was carried out, namely very high risk while those with medium risk tended to be high and medium tended to be low. After control was carried out, it was found that the risk value had decreased to predominantly green or low. Control of potential hazards in the shootcreet work area is proposed in the form of an appeal to complete PPE, use APK properly and an appeal to pay more attention to occupational safety and health in every work process. Keywords: Occupational Health and Safety, HIRARC, Risk Control